Synthesis of Nano Silver From Melastoma malabathricum Leaf Extracts Modified PVA and its Antibacterial Activity Test - Indriyani, Della Puspita; Fabiani, Verry Andre; Sari, Fajar Indah Puspita (Program Studi Kimia, Universitas Lambung Mangkurat, 2023)
Synthesis of silver nanoparticles from the extract of senduduk leaf (Melastoma malabathricum) with modified polyvinyl alcohol (PVA) has been carried out. The purpose of this study was to determine the effect of the addition of PVA on the characteristics of silver nanoparticles formed using the extract of sensaat leaf (Melastoma malabathricum). Variations in the concentration of PVA used were 0%; 0.75%; 1.5%; and 3%. Synthesis was carried out in a ratio of 1:10:1 (Extract: AgNO3: PVA) for 2 hours. The characteristics of the synthesis of nanoparticles using a UV-Vis spectrophotometer resulted in a consecutive wavelength of 414 nm; 435 nm; 438 nm; and 420 nm. To determine the particle size using Particle Size Analyzer (PSA) analysis at 0% PVA and 3% PVA with sizes obtained 61.9 nm and 216.2 nm. The average particle size using X-Ray Diffraction (XRD) analysis showed the results in the form of crystals and using the Debye-Scherrer equation to obtain the average particle size of PVA 0% 22.97 nm and PVA 3% 10.15 nm. Antibacterial activity test on silver nanoparticles used disc diffusion method, which showed that silver nanoparticles had moderate to strong antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria.Keywords: Bioreductor, senduduk leaf extract, silver nanoparticles, and polyvinyl alcohol